Perspectives on Feminist Approaches to Adult Education in International Education and Development Settings - Brigette A Herron (Adult Education Research Conference, 2019)
This empirical paper describes the preliminary results of a qualitative interview study about the feminist pedagogy of women adult educators teaching in international and development settings.
Keywords: feminist adult education; feminist pedagogy; international adult education